Iron Deficiency Generates Oxidative Stress and Activation of the SOS Response in Caulobacter crescentus - Leaden, Laura; Silva, Larissa G.; Ribeiro, Rodolfo A.; dos Santos, Naara M.; Lorenzetti, Alan P. R.; Alegria, Thiago G. P.; Schulz, Mariane L.; Medeiros, Marisa H. G.; Koide, Tie; Marques, Marilis V. (Frontiers in Microbiology, 2018)
In C. crescentus, iron metabolism is mainly controlled by the transcription factor Fur (ferric uptake regulator). Iron-bound Fur represses genes related to iron uptake and can directly activate the expression of genes for iron-containing proteins. In this work, we used total RNA sequencing (RNA-seq) of wild type C. crescentus growing in minimal medium under iron limitation and a fur mutant strain to expand the known Fur regulon, and to identify novel iron-regulated genes. The RNA-seq of cultures treated with the iron chelator 2-2-dypiridyl (DP) allowed identifying 256 upregulated genes and 236 downregulated genes, being 176 and 204 newly identified, respectively. Sixteen transcription factors and seven sRNAs were upregulated in iron limitation, suggesting that the response to low iron triggers a complex regulatory network. Notably, lexA along with most of its target genes were upregulated, suggesting that DP treatment caused DNA damage, and the SOS DNA repair response was activated in a RecA-dependent manner, as confirmed by RT-qPCR. Fluorescence microscopy assays using an oxidation-sensitive dye showed that wild type cells in iron limitation and the fur mutant were under endogenous oxidative stress, and a direct measurement of cellular H2O2 showed that cells in iron-limited media present a higher amount of endogenous H2O2. A mutagenesis assay using the rpoB gene as a reporter showed that iron limitation lead to an increase in the mutagenesis rate. These results showed that iron deficiency leads C. crescentus cells to a state of oxidative stress and activation of the SOS response, indicating an increase in DNA damage.